Influential Factors Shaping Consumer Behavior in Skincare Industry: Faktor-Faktor yang Berpengaruh dalam Membentuk Perilaku Konsumen di Industri Perawatan Kulit - Ningrum, Ridiya; Indayani, Lilik (Indonesian Journal of Innovation Studies, 2024)
This study investigates the influence of digital marketing, brand awareness, and electronic word-of-mouth (e-WOM) on consumer purchasing intentions for local skincare products in East Java, Indonesia. Employing an objective and scientific quantitative research approach, data from 97 respondents were analyzed using SPSS software. Findings reveal a significant positive impact of brand awareness and e-WOM on purchasing intentions, while digital marketing showed no significant effect. These results emphasize the importance of tailored marketing strategies in driving consumer interest and suggest avenues for future research to explore additional influencing factors. Limitations include the small sample size and potential biases in data collection. This research contributes to understanding consumer behavior dynamics in the skincare industry and informs marketing strategies for local skincare products. Highlights: 1. Analyzing digital, brand, e-WOM impact on skincare consumer behavior. 2. Brand awareness, e-WOM significantly influence consumer interest in skincare products. 3. Tailored marketing crucial for leveraging consumer preferences in skincare industry. Keywords: Consumer Behavior, Digital Marketing, Brand Awareness, Electronic Word-of-Mouth (e-WOM), Skincare Industry